On semiempirical determination of intramolecular potential function of arsine molecule; PRAHA 2006. The 19th International Conference on High Resolution Molecular Spectroscopy, Prague, Czech Republic, August 29 - September 2, 2006 - Bekhtereva E. S. Elena Sergeevna; Yukhnik (Yuhnik) Yu. B. Yuliya Borisovna; Sinitsin E. A.; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2007, 2007)
Title screen